The Impact of ESG, Capital Structure, and Asset Efficiency on Sustainable Growth Rate in Manufacturing Companies in Indonesia - Putri, Meri Anjeli; Werastuti, Desak Nyoman Sri; Dewi, Luh Gede Kusuma (International Journal Of Education, Social Studies, And Management (IJESSM), 2026)
This study aims to investigate the impact of Environmental, Social, and Governance (ESG) practices, capital structure, and asset efficiency on the Sustainable Growth Rate (SGR) of manufacturing companies listed on the Indonesia Stock Exchange between 2021 and 2024. Using secondary data from annual reports, ESG scores from Bloomberg, and financial data from the IDX website, the research explores the relationships between these factors. The results indicate that ESG and capital structure do not significantly impact SGR, suggesting that ESG efforts are largely compliance-driven and capital structure decisions are not directly linked to sustainable growth. However, asset efficiency, measured by Total Asset Turnover (TATO), was found to have a significant positive effect on SGR, highlighting the importance of efficient asset utilization in fostering long-term growth. This study contributes to understanding how internal resource management, rather than external factors, drives sustainable growth in Indonesia's manufacturing sector.